OPTIMALISASI PELATIHAN SAINS INFORMATIKA/KOMPUTER DENGAN BLENDED E-LEARNING UNTUK PERSIAPAN UTBK PADA SMA BATIK - Basiroh, Basiroh; Sudaryanto, Aninditawidagda Pandam; Rahmadzani, Rifqi Fauzi (WIDHARMA - Jurnal Pengabdian Widya Dharma, 2025)
Intensive training in preparation for the Computer-Based Written Exam (UTBK) is a strategic need to support the success of students entering higher education. One of the increasingly relevant and challenging fields is Informatics/Computer Science, which requires mastery of algorithmic concepts, programming, and computational logic. However, conventional training methods are often unable to answer the dynamics of flexible, effective, and broad-reaching learning needs. Therefore, the Blended E-Learning approach—a combination of online and face-to-face learning—is needed to optimize the training process. This objective is to design a Blended E-Learning-based training model that is adaptive, structured, and oriented towards achieving UTBK competencies in Informatics. The methodology used includes analyzing participant needs, designing curriculum, developing digital learning media, and implementing learning outcome evaluations. The results of the study show that the Blended E-Learning approach is able to increase student engagement, strengthen mastery of the material, and provide a more flexible and efficient learning space. With systematic implementation and appropriate technological support, this training model is expected to be a strategic alternative in improving students' academic readiness and expanding access to quality education in the field of Informatics/Computers.